Hydrated boroxine polyanion-induced soft amorphous oxyhalide solid state electrolytes, methods and applications

CN123018105APending Publication Date: 2026-10-30NINGBO ORIENTAL UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611144401.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种水合硼氧聚阴离子诱导的软非晶卤氧化物固态电解质及方法和应用,用以解决现有钠离子卤化物固态电解质离子电导率较低和界面兼容性欠佳的技术问题

Benefits of technology

本发明公开了一种水合硼氧聚阴离子诱导的软非晶卤氧化物固态电解质,以含结晶水的硼氧源作为氧源和结构调控剂,结晶水在机械化学过程中诱导局域结构重构并加速非晶化,使材料XRD谱图呈现宽弥散特征而无晶态衍射峰,这一完全非晶结构消除了晶界阻抗对离子传输的阻碍;同时BO2-硼氧聚阴离子的引入在非晶网络中形成柔性局域配位环境,有效降低骨架刚性,为Na+提供了连续的迁移通道,并显著降低离子迁移活化能;其次,非晶结构本身具有各向同性和无晶界特性,避免了晶态材料中晶界电阻大、空间电荷层效应明显等固有缺陷,有利于与电极之间形成紧密、均匀的固-固界面接触;此外,硼氧聚阴离子网络的引入进一步降低了材料骨架刚性,赋予材料良好的可塑性,使其在冷压成型过程中能够充分填充电极表面的微观不平整区域,有效增大真实接触面积并降低界面阻抗,同时非晶结构的柔性和局域结构可调性还有助于缓冲电池循环过程中的体积变化应力,维持界面的长期机械完整性和化学稳定性,从而协同改善了全固态电池的界面兼容性和循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018105A_ABST
    Figure CN123018105A_ABST
Patent Text Reader

Abstract

The application discloses a hydrated boron-oxygen poly-anion induced soft amorphous oxyhalide solid-state electrolyte and a method and application thereof, and belongs to the technical field of solid-state batteries. The electrolyte is an amorphous material, and has a chemical general formula of NaM(BO2) x Cl 6‑x ; wherein M is one of Hf, Nb, Al, Zr and Ta metal, and 0.05<=x<=0.20; the solid-state electrolyte is an amorphous Na-M-O-B-Cl system formed by a boron-oxygen source containing crystal water through mechanical-chemical ball milling treatment; and the crystal water in the solid-state electrolyte is used for inducing local structure reconstruction and promoting amorphization in the mechanical-chemical reaction process, so that no crystal diffraction peak appears in an X-ray diffraction spectrum of the solid-state electrolyte, and only a wide dispersion diffraction characteristic is shown. The technical problems of low ionic conductivity and poor interface compatibility of the existing sodium ion halide solid-state electrolyte are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid-state battery technology, specifically relating to a soft amorphous halide oxide solid electrolyte induced by hydrated boron oxide polyanion, its method, and its application. Background Technology

[0002] With the rapid development of large-scale energy storage and novel electrochemical energy storage technologies, all-solid-state sodium-ion batteries are considered an important development direction for next-generation energy storage systems due to their advantages such as high safety, abundant resources, low cost, and potential high energy density. Compared with traditional liquid batteries, all-solid-state sodium-ion batteries use solid electrolytes instead of flammable organic electrolytes, which can not only effectively reduce the risk of thermal runaway but also improve the battery's electrochemical stability and cycle life. Therefore, developing sodium-ion solid electrolytes with high ionic conductivity, excellent interfacial compatibility, and good air stability is key to promoting the practical application of all-solid-state sodium-ion batteries. Currently, sodium-ion solid electrolytes mainly include three major systems: oxides, sulfides, and halides. Among them, oxide solid electrolytes generally have good chemical and mechanical stability, but they usually require high-temperature sintering to achieve densification, and their room-temperature ionic conductivity is relatively low, with a large interfacial impedance. Sulfide solid electrolytes, although having high ionic conductivity and low compaction pressure requirements, suffer from poor air stability, easy generation of toxic hydrogen sulfide gas, and limited electrochemical window. In contrast, halide solid electrolytes combine high ionic conductivity, a wide electrochemical stability window, and better interfacial compatibility, showing significant application potential in the field of sodium-ion solid-state batteries.

[0003] Existing research indicates that ion transport performance can be improved to some extent through strategies such as cation doping, anion substitution, defect engineering, and crystal structure modulation. However, existing sodium-based halide systems generally suffer from limited ion diffusion channels, high structural rigidity, and low mechanochemical preparation efficiency. Furthermore, traditional crystalline halide electrolytes typically rely on long-term ball milling or high-temperature sintering processes, which are complex, energy-intensive, and difficult to densify at the interface. To further improve the performance of halide electrolytes, researchers have attempted to construct halide oxide electrolytes by introducing oxygen anions, such as using sodium peroxide (Na₂O₂) as an oxygen source to form Na-Ta-O-Cl halide oxides, which can improve ion transport performance and amorphization to some extent. However, this approach still has significant limitations: on the one hand, Na₂O₂ is expensive and has strong oxidizing properties, posing safety risks; on the other hand, existing oxygen source strategies mainly introduce oxygen elements, making it difficult to simultaneously control the amorphization degree, local structural flexibility, and continuous ion transport channels. Furthermore, the study found that the local chemical environment of the precursor has a significant impact on the mechanochemical reaction pathway and the final structure formation, especially in amorphous systems, where local structural reconstruction and ion migration channel evolution are closely related during the reaction. Therefore, relying solely on the introduction of oxygen is insufficient to achieve synergistic optimization of structure and performance, and how to utilize the precursor's own characteristics to promote local structural evolution has become a new research direction. However, existing technologies focus more on elemental doping and composition optimization, and there is a lack of systematic research and effective utilization of the role of crystal water in the precursor in local structural reconstruction, promoting rapid amorphization, and enhancing ion conduction. Summary of the Invention

[0004] The purpose of this invention is to provide a soft amorphous halide solid electrolyte induced by hydrated boron oxide polyanion, along with its method and application, to solve the technical problems of low ionic conductivity and poor interfacial compatibility of existing sodium halide solid electrolytes.

[0005] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a soft amorphous halide oxide solid electrolyte induced by hydrated boron oxide polyanion, wherein the solid electrolyte is an amorphous material with the general chemical formula NaM(BO2). x Cl 6-x ; Where M is one of the metals Hf, Nb, Al, Zr and Ta, and 0.05≤x≤0.20; The solid electrolyte is an amorphous Na-MOB-Cl system formed by mechanical and chemical ball milling of a boron-oxygen source containing water of crystallization. The water of crystallization in the solid electrolyte is used to induce local structural reconstruction and promote amorphization during the mechanochemical reaction process, so that no crystalline diffraction peaks appear in the X-ray diffraction pattern of the solid electrolyte, and only broad diffuse diffraction characteristics are exhibited.

[0006] Furthermore, the ionic conductivity of the solid electrolyte at room temperature is not less than 1.0 × 10⁻⁶. -3 S·cm -1 .

[0007] Furthermore, the ion migration activation energy of the solid electrolyte is not higher than 0.30 eV, and the Young's modulus is not higher than 2.0 GPa.

[0008] Furthermore, the ion migration activation energy of the solid electrolyte is 0.280 eV, and the Young's modulus is 1.7 GPa.

[0009] Furthermore, after the solid electrolyte is exposed to an environment with a relative humidity of 1% for 24 hours, its ionic conductivity remains at no less than 60%.

[0010] This invention also discloses a method for preparing a hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte, characterized by comprising the following steps: According to the general chemical formula NaM(BO2) x Cl 6-x Sodium source, tantalum source and boron-oxygen source are weighed as raw materials; wherein, the boron-oxygen source is sodium metaborate containing water of crystallization NaBO2·yH2O, 0≤y≤4; The weighed raw materials are mixed and carried out under an inert atmosphere or vacuum protection to obtain a soft amorphous halide oxide solid electrolyte induced by hydrated boron oxide polyanion.

[0011] Furthermore, the sodium source is at least one selected from Na2O2, Na2CO3, NaCl, NaBO2·4H2O, and Na2O; The tantalum source is at least one of TaCl5, TaN and Ta2O5; The boron-oxygen source is one or more of H3BO3, HBO2, NaBO2·4H2O, Na2B4O7, NaBO2·4H2O, and Na2O2; The ball milling speed for the mechanochemical ball milling treatment is 400~600 rpm, the ball milling time is 0.17~12 h, and the ball-to-material mass ratio is 20:1~60:1.

[0012] Further, the molar ratio of the sodium source, the metal source, and the boron-oxygen source is (0.80~1.00):(0.80~1.00):(0.05~0.20); The mechanochemical ball milling process is performed in an intermittent mode: continuous ball milling for 5 minutes followed by resting for 5 minutes constitutes one cycle.

[0013] This invention also discloses the application of the above-mentioned hydrated boron oxide polyanion-induced soft amorphous halide solid electrolyte in the preparation of all-solid-state sodium-ion batteries.

[0014] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a hydrated boron-oxygen polyanion-induced soft amorphous halide oxide solid electrolyte. A boron-oxygen source containing water of crystallization is used as both the oxygen source and the structure regulator. The water of crystallization induces local structural reconstruction and accelerates amorphization during the mechanochemical process, resulting in a material XRD pattern exhibiting broad and diffuse characteristics without crystalline diffraction peaks. This completely amorphous structure eliminates the obstruction of ion transport by grain boundary impedance; simultaneously, BO2… - The introduction of boron-oxygen polyanions creates a flexible local coordination environment in the amorphous network, effectively reducing the rigidity of the framework and providing a suitable environment for Na+. + It provides continuous migration channels and significantly reduces the activation energy of ion migration. Secondly, the amorphous structure itself is isotropic and has no grain boundary, avoiding the inherent defects of crystalline materials such as high grain boundary resistance and significant space charge layer effect, which is conducive to forming a tight and uniform solid-solid interface contact with the electrode. In addition, the introduction of boron-oxygen polyanion network further reduces the rigidity of the material skeleton and endows the material with good plasticity, enabling it to fully fill the microscopic uneven areas on the electrode surface during cold pressing, effectively increasing the actual contact area and reducing the interface impedance. At the same time, the flexibility and local structural tunability of the amorphous structure also help to buffer the volume change stress during battery cycling, maintain the long-term mechanical integrity and chemical stability of the interface, thereby synergistically improving the interface compatibility and cycle stability of all-solid-state batteries. Attached Figure Description

[0015] Figure 1 Solid electrolyte NaTa(BO2) prepared by calcining NaBO2·4H2O at different temperatures. x Cl 6-x XRD patterns; Figure 2 The present invention relates to NaTa(BO2). 0.05 Cl 5.95 NaTa(BO2) 0.10 Cl 5.90 NaTa(BO2) 0.15 Cl 5.85 And NaTa(BO2) 0.20 Cl 5.80 XRD patterns; Figure 3 NaTa(BO2) prepared in Example 10.10 Cl 5.90 XRD patterns after different ball milling times; Figure 4 Solid electrolyte NaTa(BO2) prepared by calcining NaBO2·4H2O at different temperatures. x Cl 6-x Comparison of ionic conductivity spectra; Figure 5 NaTa(BO2) prepared in Example 1 0.10 Cl 5.90 Electrochemical impedance spectroscopy; Figure 6 For NaTa(BO2) 0.05 Cl 5.95 NaTa(BO2) 0.10 Cl 5.90 NaTa(BO2) 0.15 Cl 5.85 And NaTa(BO2) 0.20 Cl 5.80 The graph showing the relationship between ionic conductivity and temperature, and the calculated activation energy value; Figure 7 NaTa(BO2) prepared in Example 1 0.10 Cl 5.90 Rate performance of all-solid-state sodium-ion batteries assembled with NaTaCl6 prepared in Comparative Example 1. Figure 8 NaTa(BO2) prepared in Example 1 0.10 Cl 5.90 Rate performance of all-solid-state sodium-ion batteries under a relatively low external pressure of 50MPa; Figure 9 NaTa(BO2) prepared in Example 1 0.10 Cl 5.90 XRD patterns of solid electrolytes exposed for different times under 1% humidity conditions. Detailed Implementation

[0016] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0017] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0018] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0019] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0020] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0021] This invention addresses the problems existing in the prior art by proposing a hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte, its preparation method, and its applications. By introducing a hydrated borate precursor, and utilizing the mechanochemical process to induce local structural reconstruction and boron-oxygen network evolution, rapid amorphization and high ionic conductivity are synergistically improved. A novel sodium-ion solid electrolyte material is developed that combines low cost, high safety, rapid construction capability, and excellent ion transport performance. Furthermore, it achieves synergistic optimization of high ionic conductivity, excellent interfacial compatibility, and good mechanical flexibility without high-temperature sintering, thus meeting the practical application requirements of high-performance all-solid-state sodium-ion batteries.

[0022] In this invention, soft amorphous refers to solid electrolytes with low Young's modulus, which are considered to be relatively soft materials.

[0023] This invention discloses a soft amorphous halide oxide solid electrolyte induced by hydrated boron-oxygen polyanion, with the general chemical formula NaM(BO2). x Cl 6-x M is one of the metals such as Hf, Nb, Al, Zr and Ta, where 0.05≤x≤0.20, and the borate precursor is NaBO2·yH2O, where 0≤y≤4.

[0024] Preferably, the ionic conductivity of the halide oxide solid electrolyte at room temperature is not less than 1×10⁻⁶. -4 S cm -1 .

[0025] Preferably, the XRD diffraction spectrum of the halide oxide solid electrolyte does not show obvious crystalline diffraction peaks, but only broad diffuse peaks.

[0026] Preferably, the ionic conductivity of the halide oxide solid electrolyte is maintained at no less than 60% after being exposed to an environment with a relative humidity of 1% for 24 hours.

[0027] Preferably, the ion migration activation energy of the halide oxide solid electrolyte is not higher than 0.30 eV; preferably, the ion migration activation energy is 0.280 eV.

[0028] The Young's modulus of the solid electrolyte is not higher than 2.0 GPa; preferably, the Young's modulus is about 1.7 GPa.

[0029] The present invention also provides applications of the above-mentioned solid electrolyte in at least one of the following aspects: (1) Improve the air stability of the positive electrode or battery; (2) Improve the first-round coulombic efficiency of the positive electrode or battery; (3) Improve the rate performance of the positive electrode or battery; (4) Improve the long-cycle performance of the positive electrode or battery; (5) Increase the loading of active material in the positive electrode or battery; (6) Increase the current density of the positive electrode or battery; (7) Improve the mechanical properties of the positive electrode or battery.

[0030] This invention also provides the above-mentioned hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte, its preparation method, and its application, comprising the following steps: Appropriate elemental raw materials are weighed according to a certain stoichiometric ratio, and thoroughly mixed by ball milling using a mechanochemical method (mechanochemical ball milling treatment) to prepare amorphous halide oxide solid electrolyte.

[0031] The raw materials for the amorphous halide electrolyte include sodium source, tantalum source and boron-oxygen source.

[0032] Furthermore, the sodium source is at least one selected from Na2O2, Na2CO3, NaCl, NaBO2·4H2O, and Na2O; Furthermore, the tantalum source is at least one selected from TaCl5, TaN, and Ta2O5; Furthermore, the boron-oxygen source is one or more of H3BO3, HBO2, NaBO2·4H2O, Na2B4O7, NaBO2·4H2O, and Na2O2.

[0033] Furthermore, the mechanical ball milling process has a rotation speed of 400~600 rpm and a time of 0.17~50 h.

[0034] Furthermore, the mechanical ball milling process is carried out under an inert atmosphere or vacuum protection.

[0035] Preferably, when y=1.6, the NaBO2·1.6H2O is obtained by heat treatment of NaBO2·4H2O at 90 °C; When y=0.4, the NaBO2·0.4H2O is obtained by heat treatment of NaBO2·4H2O at 200 °C; When y=0, the NaBO2 is obtained by heat treatment of NaBO2·4H2O at 300 °C.

[0036] Preferably, the molar ratio of the sodium source, tantalum source and boron-oxygen source is (0.80~1.00):(0.80~1.00):(0.05~0.20).

[0037] More preferably, the molar ratio of the sodium source, tantalum source and boron-oxygen source is 1.0:1.0:0.10.

[0038] Preferably, the ball milling process is performed at a rotation speed of 400-600 rpm for a duration of 0.17-12 h. More preferably, the ball milling speed is 500 rpm and the ball milling time is 8 h.

[0039] Preferably, the ball milling adopts an intermittent mode: continuous ball milling for 5 minutes followed by resting for 5 minutes constitutes a cycle.

[0040] Preferably, the ball milling process is carried out under an inert atmosphere or vacuum protection, and the ball-to-material mass ratio is 20:1 to 60:1.

[0041] More preferably, the ball-to-material mass ratio is 40:1.

[0042] This invention also provides the application of the above-mentioned hydrated boron oxide polyanion-induced soft amorphous halide oxide solid electrolyte in the preparation of all-solid-state batteries.

[0043] This invention discloses a soft amorphous halide oxide solid electrolyte induced by hydrated boron-oxygen polyanion, achieved by introducing a borate precursor containing water of crystallization. During the mechanochemical reaction process, local structural reconstruction and boron-oxygen polyanion regulation are realized, constructing an amorphous sodium-based halide oxide electrolyte with high ionic conductivity, high structural flexibility, and excellent interfacial stability. The material is prepared by introducing hydrated sodium metaborate (NaBO2·yH2O, where 0≤y≤4) into NaCl and TaCl5, the substrate materials for preparing NaTaCl6 electrolyte. A Na-Ta-BO-Cl soft amorphous halide oxide system is formed through a one-step mechanochemical method. The water of crystallization participates in the local structural evolution during the reaction process, promoting the formation of Ta-O-Cl halide-oxygen coordination structures and inducing the construction of a boron-oxygen polyanion network.

[0044] The introduction of a hydrated boron-oxygen polyanion regulation mechanism leads to a synergistic effect among crystal water, boron-oxygen polyanions, and the TaCl5 local structure: crystal water forms a transient local flow environment during the mechanochemical process, promoting rapid and uniform reaction of raw materials and significantly improving amorphization efficiency; the introduction of boron-oxygen polyanions promotes the formation of local BO networks, effectively reducing the rigidity of the material skeleton and enhancing structural flexibility, constructing more continuous sodium ion migration channels; simultaneously, the formation of the Ta-O-Cl halide-oxygen local structure further regulates the anion coordination environment, reducing Na+ ion concentration. + By migrating energy barriers and enhancing interface stability, the synergistic optimization of material ion conduction performance and structural stability can be achieved.

[0045] This invention also discloses a method for preparing the above-mentioned hydrated boron-oxygen polyanion-induced soft amorphous halide oxide solid electrolyte. This method adopts a one-step mechanochemical ball milling process, which does not require high-temperature sintering and can achieve complete amorphization of the material in a short time. It has high room temperature sodium ion conductivity, excellent air stability, and good electrode interface contact performance, and can be used in the field of high safety and high energy density all-solid-state sodium-ion batteries.

[0046] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0047] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.

[0048] Example 1 A method for preparing a hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte includes the following steps: NaCl was selected as the sodium source, TaCl5 as the tantalum source, and NaBO2·yH2O as the boron-oxygen source. Preferably, y=4, that is, NaBO2·4H2O was used to synthesize NaTa(BO2). x Cl 6-x , where x = 0.1; The specific steps are as follows: NaCl, TaCl5, and NaBO2·4H2O raw materials are weighed at a molar ratio of 1:1:0.05~0.20. Preferably, the molar ratio of sodium source, tantalum source, and boron-oxygen source is 1:1:0.10, and the total powder mass in each ball mill jar is 1 g. The ball mill jar containing the raw materials is sealed, and high-energy ball milling is performed at 500 rpm for 8 h under an inert atmosphere. The mechanochemical ball milling process adopts an intermittent mode: continuous ball milling for 5 min followed by standing for 5 min constitutes one cycle. After ball milling, the uniformly mixed material in the ball mill jar is scraped off to obtain the amorphous halide oxide solid electrolyte material (NaTa(BO2)). 0.10 Cl 5.90 ).

[0049] Example 2 A method for preparing a hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte includes the following steps: NaCl was selected as the sodium source, TaCl5 as the tantalum source, and NaBO2·yH2O as the boron-oxygen source. Preferably, y=1.6, i.e., NaBO2·1.6H2O was used. NaBO2•1.6H2O was obtained by calcining NaBO2•4H2O at 90 °C to synthesize NaTa(BO2). x Cl 6-x , where x = 0.1; The specific steps are as follows: NaCl, TaCl5, and NaBO2·1.6H2O raw materials are weighed at a molar ratio of 1:1:0.1, with a total powder mass of 1 g in each ball mill jar; the ball mill jar containing the raw materials is sealed, and high-energy ball milling is carried out at a speed of 500 rpm for 8 h under an inert atmosphere; the mechanochemical ball milling process adopts an intermittent mode: continuous ball milling for 5 min followed by standing for 5 min constitutes one cycle; after ball milling, the uniformly mixed material in the ball mill jar is scraped off to obtain the amorphous halide oxide solid electrolyte material (NaTa(BO2)). 0.10 Cl 5.90 ).

[0050] Example 3 A method for preparing a hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte includes the following steps: NaCl was selected as the sodium source, TaCl5 as the tantalum source, and NaBO2·yH2O as the boron-oxygen source. Preferably, y=0.4, i.e., NaBO2·0.4H2O was used. The NaBO2·0.4H2O was obtained by calcining NaBO2·4H2O at 200 °C to synthesize NaTa(BO2). x Cl 6-x , where x = 0.1; The specific steps are as follows: NaCl, TaCl5, and NaBO2·0.4H2O raw materials are weighed according to a molar ratio of 1:1:0.1, with a total powder mass of 1 g in each ball mill jar; the ball mill jar containing the raw materials is sealed, and high-energy ball milling is carried out at a speed of 500 rpm for 8 h under an inert atmosphere; the mechanochemical ball milling process adopts an intermittent mode: continuous ball milling for 5 min followed by standing for 5 min constitutes one cycle; after ball milling, the uniformly mixed material in the ball mill jar is scraped off to obtain the amorphous halide oxide solid electrolyte material (NaTa(BO2)). 0.10 Cl 5.90 ).

[0051] Example 4 A method for preparing a hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte includes the following steps: NaCl was selected as the sodium source, TaCl5 as the tantalum source, and NaBO2·yH2O as the boron-oxygen source. Preferably, y=0, that is, NaBO2 was used as the boron-oxygen source. The NaBO2 was obtained by calcining NaBO2·4H2O at 300 °C to synthesize NaTa(BO2). x Cl 6-x , where x = 0.1; The specific steps are as follows: NaCl, TaCl5, and NaBO2 raw materials are weighed in a molar ratio of 1:1:0.1, with a total powder mass of 1 g in each ball mill jar; the ball mill jar containing the raw materials is sealed, and high-energy ball milling is carried out at a speed of 500 rpm for 8 hours under an inert atmosphere; the mechanochemical ball milling process adopts an intermittent mode: continuous ball milling for 5 minutes followed by standing for 5 minutes constitutes one cycle; after ball milling, the uniformly mixed material in the ball mill jar is scraped off to obtain the amorphous halide oxide solid electrolyte material (NaTa(BO2)). 0.10 Cl 5.90 ).

[0052] Example 5 A method for preparing a hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte includes the following steps: NaTa(BO2) was synthesized by using NaCl as the sodium source, TaCl5 as the tantalum source, and NaBO2·4H2O as the boron-oxygen source. x Cl 6-x , where x = 0.05; The specific steps are as follows: NaCl, TaCl5, and NaBO2·4H2O raw materials are weighed at a molar ratio of 1:1:0.05, with a total powder mass of 1 g in each ball mill jar; the ball mill jar containing the raw materials is sealed, and high-energy ball milling is carried out at a speed of 500 rpm for 8 h under an inert atmosphere; the mechanochemical ball milling process adopts an intermittent mode: continuous ball milling for 5 min followed by standing for 5 min constitutes one cycle; after ball milling, the uniformly mixed material in the ball mill jar is scraped off to obtain the amorphous halide oxide solid electrolyte material (NaTa(BO2)). 0.05 Cl 5.95 ).

[0053] Example 6 A method for preparing a hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte includes the following steps: NaTa(BO2) was synthesized by using NaCl as the sodium and chlorine source, TaCl5 as the tantalum source, and NaBO2·4H2O as the boron-oxygen source. x Cl 6-x , where x = 0.15; The specific steps are as follows: NaCl, TaCl5, and NaBO2·4H2O raw materials are weighed at a molar ratio of 1:1:0.15, with a total powder mass of 1 g in each ball mill jar; the ball mill jar containing the raw materials is sealed, and high-energy ball milling is carried out at a speed of 500 rpm for 8 h under an inert atmosphere; the mechanochemical ball milling process adopts an intermittent mode: continuous ball milling for 5 min followed by standing for 5 min constitutes one cycle; after ball milling, the uniformly mixed material in the ball mill jar is scraped off to obtain the amorphous halide oxide solid electrolyte material (NaTa(BO2)). 0.15 Cl 5.85 ).

[0054] Example 7 A method for preparing a hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte includes the following steps: NaTa(BO2) was synthesized by using NaCl as the sodium source, TaCl5 as the tantalum source, and NaBO2·4H2O as the boron-oxygen source. x Cl 6-x , where x = 0.2; The specific steps are as follows: NaCl, TaCl5, and NaBO2·4H2O raw materials are weighed at a molar ratio of 1:1:0.2, with a total powder mass of 1 g in each ball mill jar; the ball mill jar containing the raw materials is sealed, and high-energy ball milling is carried out at a speed of 500 rpm for 8 h under an inert atmosphere; the mechanochemical ball milling process adopts an intermittent mode: continuous ball milling for 5 min followed by standing for 5 min constitutes one cycle; after ball milling, the uniformly mixed material in the ball mill jar is scraped off to obtain the amorphous halide oxide solid electrolyte material (NaTa(BO2)). 0.20 Cl 5.80 ).

[0055] Comparative Example 1 NaTaCl6 was prepared by using NaCl as the sodium source and TaCl5 as the tantalum source. The NaCl and TaCl5 raw materials were weighed at a molar ratio of 1:1 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar. The ball mill jar containing the raw materials is sealed and subjected to high-energy ball milling at 500 rpm for 8 hours under an inert atmosphere. After the ball milling is completed, the mixed material in the ball mill jar is scraped off to obtain NaTaCl6 material.

[0056] Comparative Example 2 NaTaOCl4 was prepared by using Na2O2 as the sodium and oxygen source and TaCl5 as the tantalum source. The raw materials Na2O2 and TaCl5 were weighed at a molar ratio of 0.5:1 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar; The ball mill jar containing the raw materials is sealed and subjected to high-energy ball milling at 500 rpm for 8 hours under an inert atmosphere. After the ball milling is completed, the mixed material in the ball mill jar is scraped off to obtain NaTaOCl4 material.

[0057] Figure 1 Solid electrolyte NaTa(BO2) was prepared by treating the NaBO2·4H2O precursor at different temperatures. x Cl 6-x The XRD patterns of the samples (Examples 1-4) are shown in the figures. As can be seen from the figures, when using the untreated NaBO2·4H2O precursor, the prepared solid electrolyte exhibits typical amorphous characteristics, and no obvious crystal diffraction peaks are observed in the XRD patterns. However, as the heat treatment temperature of the precursor increases, the water of crystallization content gradually decreases. Solid electrolytes prepared using precursors with different water of crystallization contents all exhibit obvious crystal diffraction peaks, indicating that water of crystallization plays an important role in promoting the amorphization of the material.

[0058] Figure 2 For different BO2 - NaTa(BO2) prepared by content control 0.05 Cl 5.95 (Example 5) NaTa(BO2) 0.10 Cl 5.90 (Example 1) NaTa(BO2) 0.15 Cl 5.85 (Example 6) and NaTa(BO2) 0.20 Cl 5.80 (Example 7) XRD pattern of solid electrolyte. As can be seen from the figure, the NaTa(BO2) prepared in Example 1... 0.10 Cl 5.90 The solid electrolyte did not show obvious crystal diffraction peaks, exhibiting characteristics of a completely amorphous structure.

[0059] Figure 3 NaTa(BO2) prepared in Example 1 0.10 Cl 5.90 XRD patterns of solid electrolytes under different ball milling times. The figures show that the material had essentially formed an amorphous structure after 10 min of ball milling, indicating that the boron-oxygen precursor containing water of crystallization significantly promoted the mechanochemical reaction kinetics and local structural reconstruction, accelerating the amorphization process. With further extension of the ball milling time, the local structure of the material gradually optimized, achieving better ion transport performance while maintaining the amorphous structure.

[0060] Figure 4 Solid electrolyte NaTa(BO2) was prepared by treating the NaBO2·4H2O precursor at different temperatures. x Cl 6-x The ionic conductivity comparison charts (Examples 1-4) show that the solid electrolyte prepared using the untreated NaBO2·4H2O precursor exhibits the highest ionic conductivity. As the calcination temperature of the precursor increases, the water of crystallization content gradually decreases, and the ionic conductivity of the material shows a downward trend. This indicates that water of crystallization plays an important role in promoting the formation of amorphous structures, optimizing the local ion migration environment, and improving ion transport performance.

[0061] Figure 5 NaTa(BO2) prepared in Example 1 0.10 Cl 5.90 Electrochemical impedance spectroscopy (EIS) of the solid electrolyte was performed by pressing the obtained electrolyte powder into a dense electrolyte sheet with a diameter of 10 mm in a solid-state battery test mold. A stainless steel column in the mold was used as a blocking electrode, and a 10 mV perturbation voltage was applied on a Biologic electrochemical workstation. AC impedance spectroscopy was conducted in the frequency range of 1 Hz to 7 MHz. The ionic conductivity of the material was calculated based on the measured impedance values ​​and the ionic conductivity formula. The results show that NaTa(BO2)... 0.10 Cl 5.90 Solid electrolytes exhibit the highest ionic conductivity, reaching 5.1 mS·cm at room temperature. -1 .

[0062] Figure 6 For NaTa(BO2) 0.05 Cl 5.95 (Example 5) NaTa(BO2) 0.10 Cl 5.90 (Example 1) NaTa(BO2) 0.15 Cl 5.85 (Example 6) and NaTa(BO2) 0.20 Cl 5.80 (Example 7) Relationship between ionic conductivity and temperature of solid electrolyte and corresponding activation energy results. Arrhenius curves were plotted based on the ionic conductivity results of the material at different temperatures, and the ion migration activation energy of the material was further calculated. The results show that the NaTa(BO2) prepared in Example 1... 0.10 Cl 5.90 The solid electrolyte has the lowest activation energy of 0.280 eV, indicating that the material has low Na+. + It exhibits a migration barrier and excellent ion transport dynamics.

[0063] Figure 7NaTa(BO2) prepared in Example 1 0.10 Cl 5.90 Rate performance spectra of all-solid-state sodium-ion batteries assembled with solid electrolyte and NaTaCl6 solid electrolyte prepared in Comparative Example 1, respectively. As can be seen from the figures, the NaTa(BO2) prepared in Example 1... 0.10 Cl 5.90 The all-solid-state battery assembled with a solid electrolyte exhibits excellent rate performance, maintaining 88 mAh g⁻¹ even at a high current density of 1C. -1 The discharge specific capacity was significantly higher; in contrast, the all-solid-state battery assembled with NaTaCl6 solid electrolyte without the introduction of borate hydrates exhibited only 12 mAh g⁻¹ at a 1C current density. -1 The discharge specific capacity. This is because NaTa(BO2) 0.10 Cl 5.90 Solid electrolytes possess higher ionic conductivity and continuous amorphous ion transport channels. Simultaneously, the introduction of boron-oxygen polyanions reduces the rigidity of the material framework and improves the electrode / electrolyte interface contact, thereby effectively reducing interfacial impedance and promoting Na+ absorption. + Rapid transport and improved utilization of positive electrode active material enable it to maintain a high discharge specific capacity even under high rate conditions.

[0064] Figure 8 NaTa(BO2) prepared in Example 1 0.10 Cl 5.90 Rate performance test results of the all-solid-state sodium-ion battery assembled with solid-state electrolyte under a relatively low external pressure of 10 MPa. The test results show that the all-solid-state battery assembled using the electrolyte of Example 1 exhibits good rate performance, maintaining approximately 60 mAh g⁻¹ at a current density of 0.5C. -1 The discharge specific capacity is high. This is because the soft amorphous halide oxide electrolyte constructed in this invention has a low Young's modulus and high structural flexibility, enabling good electrode / electrolyte interface contact even under low stacking pressure conditions, thereby reducing interface impedance and promoting Na+ discharge. + Fast transmission.

[0065] Figure 9 NaTa(BO2) prepared in Example 1 0.10 Cl 5.90 XRD patterns of solid electrolytes exposed to different times at 1% humidity. The figures show that after 24 hours of exposure, no obvious impurity diffraction peaks appeared, with only a few weak peak changes observed, indicating that the material exhibits good air and structural stability under low humidity conditions.

[0066] This invention discloses a soft amorphous halide oxide solid electrolyte induced by hydrated boron-oxygen polyanion. By introducing hydrated sodium metaborate (NaBO₂·yH₂O), 0≤y≤4, into a NaTaCl₆ electrolyte substrate system, and utilizing the local structural reconstruction induced by water of crystallization and the regulation by boron-oxygen polyanion during the mechanochemical process, a Na-Ta-BO-Cl soft amorphous halide oxide system is constructed. Specifically, water of crystallization promotes the formation of the Ta-O-Cl halide oxide local structure and accelerates the amorphization of the material during the mechanochemical process. Simultaneously, it facilitates the introduction of chain-like BO boron-oxygen polyanions into the material framework, enhancing the flexibility of the local structure and increasing the degree of spatial freedom, thereby reducing the rigidity of the material framework and optimizing the Na₂O-oxygen oxide structure. + Continuous migration channels and ion diffusion barriers enable a synergistic improvement in ionic conductivity and interface stability.

[0067] This invention also discloses a method for preparing the above-mentioned solid electrolyte. This method uses a one-step mechanochemical ball milling process, which does not require high-temperature sintering and can quickly achieve complete amorphization of the material. The resulting material has high room temperature sodium ion conductivity, good air stability and excellent interfacial contact performance, and is suitable for the field of high-safety, high-energy-density all-solid-state sodium-ion batteries.

[0068] In an embodiment of the present invention, the amorphous solid electrolyte has the general chemical formula NaM(BO2). x Cl 6-x M is one of the metals Hf, Nb, Al, Zr, and Ta, where 0.05 ≤ x ≤ 0.20. Preferably, sodium metaborate precursor NaBO2·4H2O containing water of crystallization is used as the boron-oxygen source, which can promote the local reconstruction and rapid amorphization of the halide-oxygen structure, thereby obtaining better ion transport performance. After component optimization, the preferred chemical composition of the solid electrolyte is NaTa(BO2). 0.1 Cl 5.9 Using the blocked electrode method at room temperature, the sodium ion conductivity reached 5.1 mS / cm. -1 Linear sweep voltammetry results indicate that the electrochemical stability window of this material is 2.3–4.0 V (vs. Na). 15 Sn4). Meanwhile, the material exhibits a Young's modulus of approximately 1.7 GPa, demonstrating good plasticity and interfacial compatibility. After exposure for 24 hours at a relative humidity of 1%, its ionic conductivity remains at 3.3 mS·cm. -1 This indicates that the material has good moisture resistance. Furthermore, XRD results show that the material exhibits typical amorphous structural characteristics.

[0069] In an embodiment of the present invention, the preparation method of the solid electrolyte includes the following steps: in an argon atmosphere glove box (H2O, O2 < 0.1 ppm), according to the target product NaTa(BO2). 0.1 Cl 5.9 The stoichiometric ratio of sodium chloride (NaCl), sodium metaborate tetrahydrate (NaBO2·4H2O), and tantalum pentachloride (TaCl5) was precisely weighed as raw materials, with a total mass of approximately 1.0 g. The raw materials were thoroughly mixed and placed in a zirconia ball mill jar, and zirconia grinding balls with a diameter of 5 mm were added, controlling the ball-to-material mass ratio at 40:1. The ball mill jar was then sealed, and high-energy mechanical-chemical ball milling was performed under an inert atmosphere. The ball milling was conducted in an intermittent mode: continuous ball milling at 500 rpm for 5 min, followed by a 5 min resting period, constituted a cycle to reduce local temperature rise during ball milling and inhibit the formation of localized ordered structures. This cycle was repeated until the cumulative ball milling time reached 8 h to obtain a uniform amorphous solid electrolyte material.

[0070] Furthermore, X-ray diffraction results showed that the material achieved complete amorphization after 10 min of ball milling, indicating that the boron-oxygen precursor containing water of crystallization significantly promoted local structural reconstruction and mechanochemical reaction kinetics. With further extension of the ball milling time, the local structure of the material gradually optimized, achieving optimal ion transport performance with the highest room-temperature sodium ion conductivity at a cumulative ball milling time of 8 h. The product obtained after ball milling can be used directly without further high-temperature sintering.

[0071] Another aspect of the present invention provides the application of the above-described soft amorphous halide oxide solid electrolyte in an all-solid-state sodium-ion battery. The prepared amorphous solid electrolyte powder is cold-pressed into a dense electrolyte sheet, which serves as the solid electrolyte separator in the all-solid-state battery, and is then combined with a sodium-tin alloy (Na₂S₂O₃). 15 A solid-state sodium-ion battery is constructed using a Sn4 anode and a layered oxide cathode, sodium nickel iron manganese oxide. Test results show that the assembled battery exhibits excellent rate performance and good cycle stability. Furthermore, due to the low Young's modulus and excellent plasticity of the amorphous electrolyte described in this invention, good electrode / electrolyte interface contact can be achieved under low applied pressure, effectively reducing interface impedance and improving battery cycle stability.

[0072] The solid electrolyte described in this invention is a soft amorphous halide oxide induced by hydrated boron-oxygen polyanion. By introducing the sodium metaborate precursor NaBO2·4H2O containing water of crystallization, the synergistic regulation of boron-oxygen polyanion and halide structure is achieved, thereby effectively adjusting the amorphization degree, local structural flexibility and sodium ion migration environment of the material, so that the material has both high ionic conductivity, excellent interfacial stability and good air resistance.

[0073] More specifically, this invention uses NaCl and TaCl5 as halide precursors and introduces a boron-oxygen source containing water of crystallization, NaBO2·4H2O, to construct a compound with the general chemical formula NaTa(BO2). x Cl 6-x A soft amorphous halide oxide solid electrolyte, wherein M is one of the metals selected from Hf, Nb, Al, Zr, and Ta, wherein 0.05 ≤ x ≤ 0.20. Preferably, after composition optimization, NaTa(BO2) is formed. 0.1 Cl 5.9 Composition. This amorphous system, through the synergistic effect of boron-oxygen polyanions and halooxygen localized structures, systematically optimizes the ion transport properties, electrochemical stability, mechanical properties, and interfacial compatibility of the material.

[0074] From the perspective of materials design mechanism, this invention achieves comprehensive performance enhancement through the synergistic effect of crystallization water assistance, localized halogen-oxygen structure reconstruction, and the introduction of boron-oxygen polyanions. Firstly, regarding ion transport performance, the crystallization water in NaBO2·4H2O promotes the formation of Ta-O-Cl localized halogen-oxygen structures during mechanochemical processes and accelerates the amorphization process. Experimental results show that the material can achieve complete amorphization after ball milling for 10 min, significantly improving reaction kinetics. The boron-oxygen polyanions gradually embed into the amorphous network, forming a more flexible local coordination environment and increasing the spatial freedom of the structure, thereby reducing the rigidity of the framework and the Na... + By migrating energy barriers and optimizing continuous ion transport channels, the material achieved optimal ion transport performance with a room-temperature sodium ion conductivity of 5.1 mS·cm when the ball milling time reached 8 h. -1 Secondly, regarding electrochemical stability, the constructed Ta-O-Cl mixed anion localization environment effectively enhances the structural stability of the material. Linear sweep voltammetry tests show that the material maintains stability at 2.3-4.0 V (vs. Na). 15 It maintains good electrochemical stability within the Sn4 range, enabling stable matching with high-voltage oxide cathodes and effectively reducing the probability of interfacial side reactions.

[0075] In terms of mechanics and interfacial stability, this invention significantly reduces the rigidity of the material skeleton by introducing a flexible boron-oxygen polyanionic network. The amorphous structure endows the material with a low Young's modulus of approximately 1.7 GPa and excellent compactability, making it easier to achieve densification during cold pressing assembly and improving solid-solid interface contact, thereby reducing interfacial impedance and enhancing cycle stability. In addition, the amorphous structure can effectively buffer local stress changes during battery cycling, suppressing interfacial cracking and contact failure.

[0076] In terms of preparation process, this invention provides a simple and efficient one-step mechanochemical synthesis method. Sodium, tantalum, and boron-oxygen sources are accurately weighed according to the general chemical formula and subjected to high-energy ball milling under an inert atmosphere. The ball milling employs an intermittent mode alternating between 500 rpm rotation speed, 5 min running time, and 5 min resting time to suppress local temperature rise and promote uniform amorphization. Rapid material construction can be achieved without traditional high-temperature sintering. A completely amorphous phase can be obtained after 10 min of ball milling, and the material exhibits the best overall electrochemical performance after 8 h of ball milling. This process has advantages such as short reaction time, low energy consumption, safe operation, low cost, and ease of large-scale preparation.

[0077] This invention addresses the technical bottleneck of existing sodium-ion solid electrolyte materials, which struggle to simultaneously achieve high ionic conductivity, low interfacial impedance, excellent air stability, and good mechanical flexibility. It provides a soft amorphous halide oxide solid electrolyte induced by hydrated boron-oxygen polyanion, its preparation method, and its applications. Existing research typically introduces Na₂O₂ as an oxygen source to construct halide oxide electrolytes, improving material structure and increasing ionic conductivity. However, Na₂O₂ is expensive, flammable, explosive, and poses high storage and handling hazards, limiting its large-scale application. This invention innovatively uses inexpensive and safe hydrated sodium metaborate (NaBO₂·yH₂O), where 0≤y≤4, as both a boron-oxygen source and an auxiliary oxygen source. Through a mechanochemical reaction, boron-oxygen polyanion introduction and local halide-oxygen structure reconstruction are achieved, forming NaTa(BO₂) with soft amorphous characteristics. x Cl 6-x Solid electrolyte materials, where 0.05≤x≤0.20, achieve a synergistic improvement in high ionic conductivity, excellent interfacial compatibility, and good air stability.

[0078] This invention systematically optimizes the ion transport performance and interfacial properties of electrolytes through the synergistic regulation of hydrated boron-oxygen polyanions and localized halooxygen structures. Firstly, regarding ion transport performance, the water of crystallization in hydrated sodium metaborate plays a solvation-like role in the mechanochemical process, promoting the full reaction between TaCl5 and the sodium source, accelerating the formation of localized Ta-O-Cl halooxygen structures, and promoting rapid amorphization of the material. Experimental results show that the material can form an amorphous structure within 10 minutes of ball milling, indicating that the water of crystallization significantly enhances the mechanochemical reaction kinetics. Simultaneously, the release of HCl gas accompanying the participation of the water of crystallization in the reaction contributes to the continuous advancement of the reaction system and structural reorganization, thereby promoting a more uniform introduction of boron-oxygen components into the material structure.

[0079] Secondly, regarding structural control and mechanical properties, the introduced BO2 - Boron-oxygen polyanions possess chain-like or locally flexible connectivity characteristics. Their introduction can effectively reduce the rigidity of the material skeleton, enhance structural flexibility, and increase the degree of freedom in local space, thereby optimizing Na…+ Continuous migration channels and reduced ion diffusion barriers. At the same time, the amorphous structure effectively eliminates grain boundary resistance and reduces the Young's modulus of the material, giving the resulting electrolyte good plasticity and interfacial compatibility.

[0080] Regarding air stability, this invention significantly improves the material's tolerance to humidity environments by constructing an amorphous halide oxide structure and utilizing the synergistic stabilizing effect of boron-oxygen polyanions. Experimental results show that after exposure to an environment with 1% relative humidity for 24 hours, the material's XRD pattern still shows no obvious impurity phase diffraction peaks, and the ionic conductivity remains at a high level, demonstrating excellent structural and air stability. This performance is significantly superior to traditional easily hydrolyzable sulfide electrolytes, while also reducing the material's dependence on ultra-harsh inert environments during storage, transportation, and battery assembly, showing promising prospects for engineering applications.

[0081] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.

Claims

1. A hydrated boron-oxygen polyanion-induced soft amorphous halide oxide solid electrolyte, characterized in that, The solid electrolyte is an amorphous material with the general chemical formula NaM(BO2). x Cl 6-x ; Where M is one of the metals Hf, Nb, Al, Zr and Ta, and 0.05≤x≤0.20; The solid electrolyte is an amorphous Na-MOB-Cl system formed by mechanical and chemical ball milling of a boron-oxygen source containing water of crystallization. The water of crystallization in the solid electrolyte is used to induce local structural reconstruction and promote amorphization during the mechanochemical reaction process, so that no crystalline diffraction peaks appear in the X-ray diffraction pattern of the solid electrolyte, and only broad diffuse diffraction characteristics are exhibited.

2. The hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte according to claim 1, characterized in that, The solid electrolyte has an ionic conductivity of not less than 1.0 × 10⁻⁶ at room temperature. -3 S·cm -1 .

3. The hydrated boron oxide polyanion-induced soft amorphous halide solid electrolyte according to claim 1, characterized in that, The ion migration activation energy of the solid electrolyte is not higher than 0.30 eV, and the Young's modulus is not higher than 2.0 GPa.

4. The hydrated boron-oxygen polyanion-induced soft amorphous halide solid electrolyte according to claim 3, characterized in that, The solid electrolyte has an ion migration activation energy of 0.280 eV and a Young's modulus of 1.7 GPa.

5. The hydrated boron oxide polyanion-induced soft amorphous halide solid electrolyte according to claim 1, characterized in that, The solid electrolyte maintains an ionic conductivity of no less than 60% after being exposed to an environment with a relative humidity of 1% for 24 hours.

6. A method for preparing a hydrated boron oxide polyanion-induced soft amorphous halide oxide solid electrolyte according to any one of claims 1 to 5, characterized in that, Includes the following steps: According to the general chemical formula NaM(BO2) x Cl 6-x Sodium source, tantalum source and boron-oxygen source are weighed as raw materials; wherein, the boron-oxygen source is sodium metaborate containing water of crystallization NaBO2·yH2O, 0≤y≤4; The weighed raw materials are mixed and carried out under an inert atmosphere or vacuum protection to obtain a soft amorphous halide oxide solid electrolyte induced by hydrated boron oxide polyanion.

7. The method for preparing a hydrated boron oxide polyanion-induced soft amorphous halide solid electrolyte according to claim 6, characterized in that, The sodium source is at least one of Na2O2, Na2CO3, NaCl, NaBO2·4H2O, and Na2O; The tantalum source is at least one of TaCl5, TaN and Ta2O5; The boron-oxygen source is one or more of H3BO3, HBO2, NaBO2·4H2O, Na2B4O7, NaBO2·4H2O, and Na2O2.

8. The method for preparing a hydrated boron oxide polyanion-induced soft amorphous halide oxide solid electrolyte according to claim 6, characterized in that, The ball milling speed for the mechanochemical ball milling treatment is 400~600 rpm, the ball milling time is 0.17~12 h, and the ball-to-material mass ratio is 20:1~60:

1.

9. The method for preparing a hydrated boron oxide mechanochemical ball milling process for polyanion-induced soft amorphous halide oxide solid electrolyte according to claim 6, characterized in that, The molar ratio of the sodium source, the metal source, and the boron-oxygen source is (0.80~1.00):(0.80~1.00):(0.05~0.20); The mechanochemical ball milling process is performed in an intermittent mode: continuous ball milling for 5 minutes followed by resting for 5 minutes constitutes one cycle.

10. The application of the hydrated boron oxide polyanion-induced soft amorphous halide solid electrolyte as described in any one of claims 1 to 5 in the preparation of all-solid-state sodium-ion batteries.